2011
DOI: 10.1002/adfm.201002729
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Crystallinity in Regioregular Poly(3‐Hexylthiophene) Thin Films and Its Impact on Field Effect Mobility

Abstract: The properties of poly(alkylthiophenes) in solution are found to have a profound impact on the self assembly process and thus the microstructural and electrical properties of the resultant thin films. Ordered supramolecular precursors can be formed in regioregular poly(3‐hexylthiophene) (P3HT) solutions through the application of low intensity ultrasound. These precursors survive the casting process, resulting in a dramatic increase in the degree of crystallinity of the thin films obtained by spin coating. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
229
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(240 citation statements)
references
References 49 publications
11
229
0
Order By: Relevance
“…[ 36 ] Polycrystalline polymers such as P3HT, F8BT, and PFO instead typically show a red shift of the absorption edge and/or more structure with vibrational sideband detail in their thin fi lm spectra compared to the good-solvent solution spectra. [ 17,36,47,48,[52][53][54] We additionally recorded the X-ray diffraction (XRD) data ( Figure S1, Supporting Information) of a 330 nm thick fi lm of PFB annealed for 1 h at 150 °C just above the glass transition temperature to encourage any potential crystallite formation (PFMO was not investigated due to limited material availability). Despite a relatively long scan time, the diffractogram showed no diffraction peaks, the spectrum being dominated by the background due to the glass substrate (we note that F8BT fi lms show clear diffraction peaks under the same experimental conditions with the same apparatus (see the Supporting Information of ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 36 ] Polycrystalline polymers such as P3HT, F8BT, and PFO instead typically show a red shift of the absorption edge and/or more structure with vibrational sideband detail in their thin fi lm spectra compared to the good-solvent solution spectra. [ 17,36,47,48,[52][53][54] We additionally recorded the X-ray diffraction (XRD) data ( Figure S1, Supporting Information) of a 330 nm thick fi lm of PFB annealed for 1 h at 150 °C just above the glass transition temperature to encourage any potential crystallite formation (PFMO was not investigated due to limited material availability). Despite a relatively long scan time, the diffractogram showed no diffraction peaks, the spectrum being dominated by the background due to the glass substrate (we note that F8BT fi lms show clear diffraction peaks under the same experimental conditions with the same apparatus (see the Supporting Information of ref.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, P3HT is polycrystalline, consisting of small crystals (aggregates) embedded in an amorphous fraction, [16][17][18] and the diode mobility varies with fi lm thickness as www.afm-journal.de www.MaterialsViews.com Figure 1. Representations of the transport state energy landscape and density of states (DOS) distribution D ( E ) for different disordered organic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a increase of crystallinity in films could enhance the carrier mobility in films [38,[52][53][54]. The increase of crystallinity is often reflected in terms of (1) enhanced absorbance attributed to ordered aggregation of chains in UV-Vis spectra [53]; (2) the higher diffraction peaks in X-ray diffraction (XRD) profiles [38,52,54] and (3) more obvious and/or ordered crystalline morphology in films such as nanofibrils [52,53], etc. Aiyar et al reported that ultrasonic vibration could increase the ordered aggregation in solution and the crystallinity in films [52].…”
Section: Crystallinity and Crystallite Alignmentmentioning
confidence: 99%
“…The increase of crystallinity is often reflected in terms of (1) enhanced absorbance attributed to ordered aggregation of chains in UV-Vis spectra [53]; (2) the higher diffraction peaks in X-ray diffraction (XRD) profiles [38,52,54] and (3) more obvious and/or ordered crystalline morphology in films such as nanofibrils [52,53], etc. Aiyar et al reported that ultrasonic vibration could increase the ordered aggregation in solution and the crystallinity in films [52]. With increasing vibration time, the 0-0 absorbance in solution and films and the (100) peak height increased until reaching a platform after vibrating for 5 min, accompanied by the development of fibrillar morphology of films.…”
Section: Crystallinity and Crystallite Alignmentmentioning
confidence: 99%
“…Hence, disentanglement results in facile pre-aggregation of a large number of nuclei with uniform size distribution, leading -among other things -to a reduction of the specific viscosity of the solution and to easier diffusivity of pre-aggregates and chains. 12,31 During solution drying, disentangled chains and pre-aggregates therefore more easily assemble into structures exhibiting enhanced backbone planarity, lamellar thickness and extended π-π* conjugation. 32 Molecular self-assembly during solution-casting can be influenced by surface functionalization with a SAM, an effect widely recognized in solution-processed small-molecule organic semiconductors.…”
Section: Introductionmentioning
confidence: 99%